1997
DOI: 10.1021/la970294a
|View full text |Cite
|
Sign up to set email alerts
|

Particle Clustering and Pattern Formation during Electrophoretic Deposition:  A Hydrodynamic Model

Abstract: Clustering of latex particles 4−10 μm in diameter during and after electrophoretic deposition of the particles onto flat electrodes has been reported by Böhmer (Langmuir 1996, 12, 5747). The particles interacted over length scales comparable to their size in the formative stages of the clusters. Combinations of two or more clusters already deposited approached each other to form larger agglomerates. A model based on electroosmotic flow about charged particles near surfaces is developed here to explain these ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
270
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(283 citation statements)
references
References 11 publications
9
270
0
1
Order By: Relevance
“…7b). The maximum thickness observed at this potential was 16 Ϯ 2 m. The changes in microcolony features and distribution can be explained if the synergic influence of the modified growth of individual cells, the electrophoretic effects on charged bacteria, and the electro-osmotic induction of cell clustering (2,13,15) is considered. All these processes are thought to contribute to the formation of tightly packed microcolonies under positive polarization ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…7b). The maximum thickness observed at this potential was 16 Ϯ 2 m. The changes in microcolony features and distribution can be explained if the synergic influence of the modified growth of individual cells, the electrophoretic effects on charged bacteria, and the electro-osmotic induction of cell clustering (2,13,15) is considered. All these processes are thought to contribute to the formation of tightly packed microcolonies under positive polarization ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…[1][2][3] These flows exert hydrodynamic forces on the spheres, and their motions, in turn, redirect the flows. [2][3][4][5] We previously reported 6,7 that the interplay of microscopic electrohydrodynamic flows around individual spheres can give rise to large-scale convective instabilities characterized by highly organized flow patterns involving thousands of spheres. These colloidal electroconvective patterns form at biases just above the threshold for steady electrolysis, and their structure depends on the properties and concentration of the colloidal spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Phase transitions and clustering instability of the electrostatically driven granular gas were found. The studies of self-assembly of colloidal particles in aqueous solutions revealed the importance of self-induced electrohydrodynamic (EHD) convective flows on the formation of various precipitate states [4,7,8,9,10]. Ordered clusters of particles vibrated in liquid were studied in Ref.…”
mentioning
confidence: 99%